Cileungsi and the Indonesian War of Independence: A Local Historical Study of West Java - Agung; Sulistiyono, Singgih Tri; Rochwulaningsih, Yety; Rinardi, Haryono (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2026)
ABSTRACT The Indonesian War of Independence is commonly examined through major events in urban political and military centers, resulting in the marginalization of peripheral regions within national historiography. This article aims to analyze the role of Cileungsi, a peripheral area in West Java, during the Indonesian War of Independence between 1945 and 1950, with particular attention to its geographical position, forms of local resistance, and social consequences of the conflict. This study employs the historical method, consisting of heuristic research, source criticism, interpretation, and historiography, combined with a historical-sociological approach. The sources include colonial and post-independence archives, military and administrative reports, contemporary newspapers, and local oral traditions. The findings demonstrate that Cileungsi played a strategic role as a connective corridor between Batavia, Buitenzorg, and eastern West Java, functioning as a base for guerrilla warfare, logistical support, and popular resistance. Local actors such as community leaders, religious figures, and youth militias actively participated in resistance efforts, often operating outside formal military structures. Furthermore, the revolutionary period profoundly transformed the social, economic, and cultural life of the local population. This study concludes that Cileungsi was not a passive peripheral space but an integral component of the Indonesian revolutionary struggle, highlighting the importance of local history in constructing a more inclusive and balanced national historiography.